2017
DOI: 10.1038/s41598-017-07459-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic frustration induced large magnetocaloric effect in the absence of long range magnetic order

Abstract: We have synthesized a new intermetallic compound Ho2Ni0.95Si2.95 in a single phase with a defect crystal structure. The magnetic ground state of this material found to be highly frustrated without any long range order or glassy feature as investigated through magnetic, heat capacity and neutron diffraction measurements. The interest in this material stems from the fact that despite the absence of true long range order, large magnetocaloric effect (isothermal magnetic entropy change, −ΔSM ~ 28.65 J/Kg K (~205.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 46 publications
4
35
0
Order By: Relevance
“…It may be noted here that although many similar R 2 TX 3 type of compounds have been reported in literature to form along with a secondary phase which were of R T 2 X 2 type 16 , in contrast to PrNiSi 2 found in our system. We had earlier reported similar RNiSi 2 type of secondary phase in R 2 NiSi 3 ( R  = Ho, Tm) compounds 6,17 . These additional XRD peaks, however, can not be removed by thermal annealing as the single phase compounds could be synthesized only by deliberately tweaking the proportion of initial stoichiometry by subtracting the volume fraction of elements present in the secondary phase.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…It may be noted here that although many similar R 2 TX 3 type of compounds have been reported in literature to form along with a secondary phase which were of R T 2 X 2 type 16 , in contrast to PrNiSi 2 found in our system. We had earlier reported similar RNiSi 2 type of secondary phase in R 2 NiSi 3 ( R  = Ho, Tm) compounds 6,17 . These additional XRD peaks, however, can not be removed by thermal annealing as the single phase compounds could be synthesized only by deliberately tweaking the proportion of initial stoichiometry by subtracting the volume fraction of elements present in the secondary phase.…”
Section: Resultsmentioning
confidence: 56%
“…It may be mentioned here that, we have earlier reported that the coherence length of the magnetically ordered phase of Er 2 NiSi 3 at 0.8T N  ~ 143 Å (~35 unit cells) and tend to saturate at low temperature with the value of 250 Å (~60 unit cells) 5 . The long range magnetic ordering could not be seen in Ho 2 Ni 0.95 Si 2.95 as the coherence length at 1.5 K is about 35 Å (~8 unit cells), although magnetization and heat capacity studies reveal magnetic clusters appear to form below 3.6 K 6 . The temperature dependence of ac susceptibility peak at 3.6 K remain insensitive to change in frequency, which further reveals magnetic clusters in Ho 2 Ni 0.95 Si 2.95 even do not exhibit inter-cluster correlations, therefore no cluster-glass phenomenon could be seen either.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Rare earth based magnetic materials have attracted a significant attention of the researchers due to their complex phase transition among different magnetic phases under the influence of temperature, magnetic field and pressure. During the last few years, a group of rare earth based bulk intermetallic compounds have been extensively studied due to the exhibition of large magnetocaloric effect (MCE) [1,2,3,4,5,6,7,8,9]. MCE is an intrinsic thermodynamical phenomena of every magnetic materials where change in material temperature occurs under the influence of external magnetic field under adiabatic condition.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the ternary intermetallic compounds of the RTX family, where the R − rare‐earth, T, and X − different d ‐ and p ‐elements, respectively, have a wide variety of magnetic and electronic properties, presenting fundamental and practical interest, see recent reviews and other studies. A number of unusual physical phenomena observed in such compounds, for example, the giant magnetocaloric effect and magnetoresistance, are considered to be related with the peculiarities of hybridization of the localized 4 f ‐states of rare‐earth metals and conduction electrons in the electronic system.…”
Section: Introductionmentioning
confidence: 99%